A cultura maker na formação continuada de professores da rede municipal de educação de Pentecoste - CE: experiências e resultados - Ribeiro Neto, João (2024)
The objective of this study was to investigate the Maker Culture in the Continuing Education of teachers in the Municipal Education Network of Pentecoste/CE. In order to meet the objectives of this research, we established the following guiding question: What are the main perceptions, impacts and pedagogical practices of eleven (11) teachers from the Municipal Education Network of Pentecoste/CE after participating in a workshop focused on the maker culture with a constructionist approach through the application of didactic sequences? To achieve the results, we used a qualitative research approach through semi-structured questionnaires to analyze and interpret the data from the workshop participants. Therefore, questionnaires were applied before the workshop and after the workshop, both with the intention of mapping prior knowledge, gaps, evaluating the intervention and verifying whether the objectives were achieved, respectively. We also applied questionnaires that evaluated the workshop and the performance of the mediating teacher. The responses were collected through the Google Forms tool and, for a more detailed analysis of the data, we used graphs and tables. Furthermore, to answer the subjective questions regarding the research questions, we used Bardin's Content Analysis (1977). In summary, the results show that the maker culture, with its constructionist approach and didactic sequences, offers enormous potential for reflection and transformation of pedagogical practice, but it is still little explored in the continuing education of teachers. In addition, the application of constructionist didactic sequences from the perspective of the maker culture is still little explored in the training of teachers in the Municipal Education Network of Pentecoste/CE. It is also evident that the maker culture, with the use of 3D printers and digital models, expands the teacher's repertoire, as well as enriches the teaching-learning process, enabling teachers to materialize abstract concepts in a more concrete and engaging way, overcoming the limitations of traditional means. Another point that is reflected in the teachers' responses is the traditional teaching instituted within the school, which in turn is the result of traditional pedagogical practices learned during their professional training. In short, the workshop had a positive impact and provided opportunities for new ideas and in-depth reflections, significantly expanding teachers' pedagogical practices, as well as fostering the emergence of innovative ideas and the sharing of significant experiences associated with project development, problem-solving, and curricular components. We can also emphasize that the workshop brings a new perspective to the classroom.